2012
DOI: 10.1136/bmjopen-2011-000657
|View full text |Cite
|
Sign up to set email alerts
|

Non-response in a nationwide follow-up postal survey in Finland: a register-based mortality analysis of respondents and non-respondents of the Health and Social Support (HeSSup) Study

Abstract: ObjectiveTo examine difference in mortality between postal survey non-respondents and respondents.DesignA prospective cohort study with baseline survey in 1998 and comprehensive linkage to national mortality registers until 2005, the Health and Social Support study.SettingA population-based postal survey of the working-aged population in Finland in 1998.ParticipantsThe original random sample comprised 64 797 working-aged individuals in Finland (20–24, 30–34, 40–44, 50–54 years of age; 32 059 women and 32 716 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
1
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 21 publications
(25 reference statements)
4
54
1
4
Order By: Relevance
“…Our finding of only approximately one in four patients continuing to use the brace regularly for more than a year may represent a best-case scenario, for the brace, in that we used only one experienced orthotist who communicated regularly with the prescribing surgeon, gave all patients a no-charge 1-month trial with the brace, invited the patients to have free refittings as needed, and permitted cotreatments (including joint injections and nonnarcotic analgesics) as desired by the patients. We surmise patients who declined to participate in the survey were more likely to be unhappy with the brace treatment, as there are data to suggest health states of nonresponders are lower than those of responders in survey studies [20], again emphasizing, if anything, our results represented a best-case estimate of success with the unloader brace. Other studies have varied in terms of reported compliance rates with time.…”
Section: Discussionmentioning
confidence: 83%
“…Our finding of only approximately one in four patients continuing to use the brace regularly for more than a year may represent a best-case scenario, for the brace, in that we used only one experienced orthotist who communicated regularly with the prescribing surgeon, gave all patients a no-charge 1-month trial with the brace, invited the patients to have free refittings as needed, and permitted cotreatments (including joint injections and nonnarcotic analgesics) as desired by the patients. We surmise patients who declined to participate in the survey were more likely to be unhappy with the brace treatment, as there are data to suggest health states of nonresponders are lower than those of responders in survey studies [20], again emphasizing, if anything, our results represented a best-case estimate of success with the unloader brace. Other studies have varied in terms of reported compliance rates with time.…”
Section: Discussionmentioning
confidence: 83%
“…Por el contrario, el sexo no aparece como un factor asociado con la no respuesta, tal y como se describe en algunos trabajos 14,30,31 y, a diferencia de lo descrito por otros autores 9,10,17,18,32,33 , tampoco los hábitos o conductas de salud y la utilización de servicios sanitarios .…”
Section: Discussionunclassified
“…Diversos trabajos han investigado las características (sociodemográficas, hábitos de salud, estado de salud autopercibida) de los respondedores en comparación con quienes no responden y el posible efecto de las diferentes características sobre la validez de los resultados de una encuesta de base poblacional, con conclusiones divergentes [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] . Algunos autores consideran que la influencia de la no respuesta es poco relevante sobre los resultados, siendo estos extrapolables a la población general 12,[14][15][16][17]23 .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Of these 19 629 also responded at the follow-up in 2003 (response rate 75.8%). Analysis of non-responders showed a good compatibility of the HeSSup sample with the Finnish population [3,4]. The concurrent joint Ethics Committee of the University of Turku and the Turku University Central Hospital considered approval not necessary for a normal cohort study, but all participants were requested to sign a consent form containing information about the study and to grant permission to allow subsequent studies with the same data set and possibility to link with national health registries.…”
Section: Methodsmentioning
confidence: 99%